STUDI DESAIN PEMANFAATAN DRUM BEKAS MENJADI TANGKI SEPTIK PASANG SURUT - Aksin Munawar; Suparmi Suparmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Feces waste water disposal which do not qualify cause loss of environmental quality such as interference with the aesthetic form of smell and a polluted environment. There was also other effect such as bacteriological contamination on water resource and the rivers. This condition will not occur if acces to sanitation such  as toilets helthy at anytime, either normal or emergency condition. This acces is often faced obstacles, in particular on the discharge into the septic tank and absorption wells for those who live in tidal areas.            Acces healthy toilets is a shared responbility  between the government and the public in accordance with PERMENKES No. 3 in 2014 abaout Total Sanitation of Community Based (STMB).  Under certain condition the efforts made are often faced with specific problems such as Geographical condition, people I the swamp area, Tidal and or any other emergencies such as natural diseasters, Gathering of people a that, and others. So  that, facilities necessary with a special design made with appropriate technology approach.            The study used a prospective cohort study design with the approach of the observation of the physical condition of the septic tank. While the quality by checking the parameters of TSS and BOD wastewater samples were taken from the outlet 4 time examined the laboratory of BLHD in Jambi Province.            TSS content on compartment A of 178 mg/l whereas in compartment B are in the range between 45 mg/l  amount up to 310 mg/l BOD content on compartment A of 281 mg/l whereas in compartment in the range between 72 mg/l amount up to 846 mg/l.            The high parameters of TSS and BOD in the test of the 2 nd possible because the decomposition of organic materialby microorganisms isnot optimal. While decreased dramatccally in 3 sampledue to the absence increase feces in  a relatively long time.            Altough in general the average TSS and BOD levels are still above the water quality standart of waste in accordance of LH PERMEN No. 3 in 2012 but the septic tank can be used for people in the tidal area of the disposal of feces directly into the environment. Utilizationof drums into a septic tank can lead to the achievement of acces to the toilet in order to achieve the first pillar of STMB.Further studies are needed to design an experiment that conditioned the continuity of feces waste stream and the addition of various media bioflm.Keywords : Drums, Septic tank, BOD, TSS, The density of flies, Smell.